2012
DOI: 10.2147/ijn.s34612
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oral bioavailability of a sterol-loaded microemulsion formulation of Flammulina velutipes, a potential antitumor drug

Abstract: Purpose:To investigate the growth inhibition activity of Flammulina velutipes sterol (FVS) against certain human cancer cell lines (gastric SGC and colon LoVo) and to evaluate the optimum microemulsion prescription, as well as the pharmacokinetics of encapsulated FVS. Methods: Molecules present in the FVS isolate were identified by gas chromatography/mass spectrometry analysis. The cell viability of FVS was assessed with methyl thiazolyl tetrazolium (MTT) bioassay. Based on the solubility study, phase diagram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Thus, F. velutipes may represent an important food source for humans or other animals to obtain sufficient amounts of the essential fatty acids our body requires but which cannot be synthesized. Many studies also demonstrated that sterols extracted from F. velutipes possess antiproliferative activity against several cancer cell lines and have the potential to be developed as chemotherapeutic agents (Yi et al, 2012, 2013a); while mycosterol, derived from the extract of F. velutipes , exhibits potent hypolipidemic activity (Yeh et al, 2014). …”
Section: Chemical Composition and Nutritional Value Of F Velutipesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, F. velutipes may represent an important food source for humans or other animals to obtain sufficient amounts of the essential fatty acids our body requires but which cannot be synthesized. Many studies also demonstrated that sterols extracted from F. velutipes possess antiproliferative activity against several cancer cell lines and have the potential to be developed as chemotherapeutic agents (Yi et al, 2012, 2013a); while mycosterol, derived from the extract of F. velutipes , exhibits potent hypolipidemic activity (Yeh et al, 2014). …”
Section: Chemical Composition and Nutritional Value Of F Velutipesmentioning
confidence: 99%
“…It showed potent antiproliferative activity against human SGC cells (stomach cancer cells) with an IC 50 of 11.99 μg/mL, HepG-2 cells with IC 50 at 9.3 μg/mL, A549 lung cancer cell with IC 50 at 20.4 μg/mL and U251 glioblastoma with IC 50 at 23.42 μg/mL (Yi et al, 2012, 2013a,b). Studies have also been done to improve the bioavailability, biodistribution and solubility of sterols from F. velutipes through encapsulation in liposomes, mixed micelles nanoformulation and microemulsion (Yi et al, 2012, 2013a,b). …”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Flammulina velutipes ( F. velutipes ) has been recognized as a model industrial basidiomycete; it is one of the most commonly used edible fungi, serving as an excellent source of vitamins, amino acids, polysaccharides, fibre, terpenoids, phenolic acids, steroids, fatty acids and other metabolites, and is widely cultivated worldwide [25]. Compounds with pharmaceutical value can be isolated from the fruiting bodies or mycelia of F. velutipes , including anti-inflammatory and immunomodulatory proteins [6], antitumour, antioxidant and acetylcholinesterase inhibitory polysaccharides, antitumour agglutinins and immunomodulatory compounds [7], antimicrobial terpenoids [8], and antitumour and antioxidant sterols [9, 10]. The active antitumour sterols include ergosterol, 22,23-dihydroergosterol, ergosta-5,8,22-trien-3-ol and ergo-8(14)-ene-3-ol [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The active antitumour sterols include ergosterol, 22,23-dihydroergosterol, ergosta-5,8,22-trien-3-ol and ergo-8(14)-ene-3-ol [11, 12]. The chemical composition of sterols is mainly ergosterol (54.8%) and 22,23-dihydroergosterol (27.9%) [10]. GC-MS or HPLC studies of saponification extraction have revealed that the ergosterol content in F. velutipes was 35.5 mg/100 g in wet weight or 68.0 mg/100 g in dry weight [13, 14].…”
Section: Introductionmentioning
confidence: 99%